Altered Nutrient Uptake Causes Mitochondrial Dysfunction in Senescent CD8+ EMRA T Cells During Type 2 Diabetes - Callender, Lauren A.; Carroll, Elizabeth C.; Garrod-Ketchley, Conor; Schroth, Johannes; Bystrom, Jonas; Berryman, Victoria; Pattrick, Melanie; Campbell-Richards, Desiree; Hood, Gillian A.; Hitman, Graham A.; Finer, Sarah; Henson, Sian M. (Frontiers in Aging, 2021)
Mitochondrial health and cellular metabolism can heavily influence the onset of senescence in T cells. CD8+ EMRA T cells exhibit mitochondrial dysfunction and alterations to oxidative phosphorylation, however, the metabolic properties of senescent CD8+ T cells from people living with type 2 diabetes (T2D) are not known. We show here that mitochondria from T2D CD8+ T cells had a higher oxidative capacity together with increased levels of mtROS, compared to age-matched control cells. While fatty acid uptake was increased, fatty acid oxidation was impaired in T2D CD8+ EMRA T cells, which also showed an accumulation of lipid droplets and decreased AMPK activity. Increasing glucose and fatty acids in healthy CD8+ T cells resulted in a fragmented mitochondrial morphology, similar to CD8+ EMRA T cells in T2D. The resulting mitochondrial changes are likely to have a profound effect on T cell function. Consequently, a better understanding of these metabolic abnormalities is crucial as metabolic manipulation of these cells may restore correct T cell function and help reduce the impact of T cell dysfunction in T2D.